Fully Transparent Epitaxial Oxide Thin‐Film Transistor Fabricated at Back‐End‐of‐Line Temperature by Suboxide Molecular‐Beam Epitaxy - Felix V.E. Hensling; Patrick Vogt; Jisung Park; Shun‐Li Shang; Huacheng Ye; Yu‐Mi Wu; Kathleen Smith; Veronica Show; Kathy Azizie; Hanjong Paik; Debdeep Jena; Huili G. Xing; et al. (Advanced Electronic Materials)
Abstract Transparent oxide thin film transistors (TFTs) are an important ingredient of transparent electronics. Their fabrication at the back‐end‐of‐line (BEOL) opens the door to novel strategies to more closely integrate logic with memory for data‐intensive computing architectures that overcome the scaling challenges of today's integrated circuits. A recently developed variant of molecular‐beam epitaxy (MBE) called suboxide MBE (S‐MBE) is demonstrated to be capable of growing epitaxial In2O3 at BEOL temperatures with unmatched crystal quality. The fullwidth at halfmaximum of the rocking curve is 0.015° and, thus, ≈5x narrower than any reports at any temperature to date and limited by the substrate quality. The key to achieving these results is the provision of an In2O beam by S‐MBE, which enables growth in adsorption control and is kinetically favorable. To benchmark this deposition method for TFTs, rudimentary devices were fabricated.